2016
DOI: 10.1007/s12192-016-0669-5
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides alleviate myocardial ischemia-reperfusion injury via attenuation of oxidative stress and preservation of mitochondrial function in rat heart

Abstract: Gypenosides (GP) are the predominant components of Gynostemma pentaphyllum, a Chinese herb medicine that has been widely used for the treatment of chronic inflammation, hyperlipidemia, and cardiovascular disease. GP has been demonstrated to exert protective effects on the liver and brain against ischemia-reperfusion (I/R) injury, yet whether it is beneficial to the heart during myocardial I/R is unclear. In this study, we demonstrate that pre-treatment with GP dose-dependently limits infarct size, alleviates I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…We examined cell viability under conditions of oxidative stress and found that 50-200 μM Gp significantly increased the viability of RGC cultures exposed to H 2 O 2 . Our results were consistent with previous studies, which show that Gp reduced ROS levels during ischemia-reperfusion injury, and protect RGCs from oxidative stress in a concentration-dependent manner (Yu et al 2016a).…”
Section: Discussionsupporting
confidence: 94%
“…We examined cell viability under conditions of oxidative stress and found that 50-200 μM Gp significantly increased the viability of RGC cultures exposed to H 2 O 2 . Our results were consistent with previous studies, which show that Gp reduced ROS levels during ischemia-reperfusion injury, and protect RGCs from oxidative stress in a concentration-dependent manner (Yu et al 2016a).…”
Section: Discussionsupporting
confidence: 94%
“…In this regard, the maintenance of the mitochondrial membrane integrity inhibited the release of cytochrome c from the mitochondria into the cytosol. This further demonstrated the role of gypenosides from G. pentaphyllum as a cytoprotective agent against acute myocardial infarction and reperfusion injury (Yu et al, 2016a).…”
Section: In Vivo Preclinical Evaluations Of G Pentaphyllummentioning
confidence: 71%
“…GPS is a bioactive component with various pharmacological properties and beneficial clinical effects on conditions including hyperlipoproteinemia, 1 cancer, [2][3][4] hepatitis, 5 and cardiovascular disease. 6 However, like other saponins, GPS are easily degraded due to their sensitivity to environmental factors, such as heat, light, and oxygen and are limited in their bioavailability and clinical applications owing to their poor lipid and water solubilities and hemolytic properties. Recent studies have focused on strategies to enhance the stability and bioavailability of GPS, which include the use of microcapsules and liposomes.…”
Section: Introductionmentioning
confidence: 99%